2022
DOI: 10.1111/rda.14130
|View full text |Cite
|
Sign up to set email alerts
|

Effects of different concentrations of zinc oxide nanoparticles on the quality of ram cauda epididymal spermatozoa during storage at 4°C

Abstract: Zinc oxide nanoparticles (ZnO‐NPs) are known for their antioxidant effects. In this study, ZnO‐NPs were synthesized using aqueous extract of Maclura pomifera fruit; then, their effects on the quality of ram cauda epididymal spermatozoa were evaluated during storage at 4°C. ZnO‐NPs formation was characterized by ultraviolet–visible spectroscopy (UV–vis), energy dispersive spectroscopy (EDX), field emission scanning electron microscopes (FE‐SEM) and Fourier transform infrared (FTIR) spectroscopy. Cytotoxicity re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 54 publications
0
1
0
Order By: Relevance
“…Another study refers to action of zinc oxide in low dose made positive results on ram epididymal sperms after storage in cooled way, these result disagreement with present study and this may be due to that low dose zinc oxide NPS improve sperm quality and also for different source of nanoparticles [26].…”
Section: Zinc Oxide Nanoparticlescontrasting
confidence: 98%
See 1 more Smart Citation
“…Another study refers to action of zinc oxide in low dose made positive results on ram epididymal sperms after storage in cooled way, these result disagreement with present study and this may be due to that low dose zinc oxide NPS improve sperm quality and also for different source of nanoparticles [26].…”
Section: Zinc Oxide Nanoparticlescontrasting
confidence: 98%
“…Many reports refers to using Zinc oxide NPs to improved semen characteristics and reproductive performance in Ram [9], buffalo [10], camel [11], human [12], rabbit [ 13] and rooster [14], also these reports mention the positive effect of Zinc oxide NPs and improving sperms quality during storage by keep plasma membrane integrity, mitochondrial function, improved sperm progressive motility, viability, maintained ultrastructure morphology, decrease apoptosis and increase sperm count [15], but its effect was dose-depended according in different papers. There were a few reports explain exposure of Cerium Oxide (CeO 2 NPs) on Awassi epididymal sperms characteristics, Falachi et al, [16] reveled CeO 2 NPs beneficial effects on kinematic and morphologic parameters on ram semen after 96 hrs of storage at 4C 0 .…”
Section: Introductionmentioning
confidence: 99%
“…It was also observed that the mixture of ZnO and TiO 2 NPs induced more sperm abnormalities than either of them (Ogunsuyi et al, 2020). In a recent study on ram epididymal spermatozoa, it was observed that there were some beneficial effects (increased sperm total motility, viability, DNA and membrane integrity, TAC and SOD with reduced lipid per‐oxidation) of ZnO NPs supplementation in sperm extender during oxidative stress conditions and cooled storage (Soltani et al, 2022). It is evident that the studies on effects of ZnO NPs on male germ cells are still scarce and need further validation at in vitro and in vivo levels.…”
Section: Toxicities Of Different Metallic Nps To Spermatozoamentioning
confidence: 99%
“…Among other functions, Zn plays a vital role in regulating redox homeostasis (Atrian and Capdevila 2013), which is crucial for sperm survival, particularly for the stallion (Gibb and Aitken 2016;Pena ˜ et al 2022). Previous research on the effects of Zn supplementation in equine semen extenders is limited (Ghallab et al 2017), but a protective role of Zn in sperm samples has been described in species such as roosters (Khodaei-Motlagh et al 2022), bulls (Gualtieri et al 2014), humans (Isaac et al 2017), ram (Soltani et al 2022), and dog (Fayez et al 2023) among others.…”
Section: Introductionmentioning
confidence: 99%